(untitled) (Scientific journal of the Fergana State University, 2023)
This article focuses on the poetics of the novels of the German writer Herta Muller, such as “Herztier” and “Atemschaukel”, mainly with an analysis of metaphors in the writerʼs works and a demonstration of writing skills. Currently, the German writer Herta Muller attracts thinkers of world literature to the poetics of her novels. Through the main characters and participants of the episodes involved in the novels, Herta Muller was able to explain her philosophy.